The role and principles importance of the biys court activity as an institution of Kazakh customary law for modern legal relations - Turlayev, A.; Akhmetova, N. (Bulletin of the Karaganda University “Law Series”, 2020)
The article reveals the unique customs and traditions of the Kazakh people, which were based on the principles that lay down the legal regulation of social relations, condition social justice in resolving disputes and other conflicts arising in the process of economic activity and everyday life. The principles on which the Kazakh society was founded, which are the basis of Kazakh customary law in modern conditions can be char act erased as humanistic. On the basis of these principles, the formation of a fundamental principles number is possible that, taking into account the historical roots, will allow modernization of modern law. Despite the fact that the principles of customary law worked effectively in the historical period of the existence of the Kazakh Khanate and semi-nomadic farming, in modern conditions it is possible to modernize and use them in the modern legal culture as a historically established system of authoritative legal values. These are legal values that stipulate certain types of legal punishments and rewards, principles of mutual relations of the parties in civil, family, labor and other legal relations based on the equality of the parties and voluntary rights and obligations determination. The article substantiates the possibility of using the principles of adversariality, transparency, the predominance of property responsibility as the main punishment type, and the wider use of legal incentive measures in modern conditions.